Skrining Fitokimia Daun Sukun (Artocarpus Altilis) - Fit, Safitri Rahmat; Siti Zuraidah; Deswita Deswita; Kristina Tresia Leto (International Forum of Researchers and Lecturers, 2025)
Breadfruit (Artocarpus heterophyllus) leaves are widely used in traditional medicine in Southeast Asia. Phytochemical screening of breadfruit leaves showed that the plant is rich in chemical contents that have potential as a source of natural medicine. The biological activity of breadfruit leaf phytochemicals showed potential in the treatment of various diseases. The benefits of phytochemicals (Development of natural medicines, Discovery of new chemical compounds, Development of cosmetic and food products, Improvement of quality of life through the use of natural products and Conservation of rare and endemic plants). this research uses the method Phytochemical screening of breadfruit leaves involves several stages: Extraction, Fractionation, Identification. The results stated that breadfruit leaves contain Steroid / Terpenoid compounds which indicate positive results in concentrated green, Saponin negative results that only precipitate not, Tannin positive results in blackish color, Flaphonoid positive results in red color and Alkoloid positive results in brown color.